CRITICAL THINKING IN BUILDING ETHICAL LEADERSHIP IN THE DIGITAL ERA - Muhammad Bagas F; Salminawati; Indra Sakti Siagian; Muhammad Halomoan (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The digital era presents significant challenges in managerial and leadership practices, where leaders are not only required to possess technical skills but also the ability to think critically and ethically. Digital transformation impacts decision-making within organizations, with technologies like artificial intelligence and big data often raising moral dilemmas. Therefore, critical thinking and ethical leadership become essential foundations for guiding decisions that consider social and moral implications. Critical thinking in management encompasses not only data analysis and strategy effectiveness but also the ability to evaluate the moral consequences of each decision. Meanwhile, ethical leadership focuses on moral responsibility, transparency, and social justice. This study aims to develop a conceptual model linking critical thinking and ethical leadership through a qualitative-descriptive approach with a conceptual literature study. It is expected that this research will contribute to value-based leadership theory and provide guidance for leaders in the digital era to apply ethical principles in management. Through the "Critical-Ethical Leadership Framework (CELF)" model, this research offers insights into how leadership can better focus on human values while helping organizations adapt to technology in an ethical manner.